Endovascular Aortic Repair (EVAR) Method in The Management of Abdominal Aortic Aneurysm - Sebayang, Abed Nego Okthara; Hidayat, Niko Azhari (Talenta Publisher, 2020)
Aortic disease is a collection of diseases of the aorta, which includes aortic aneurysms; acute aortic infections consisting of aortic dissection, intramular hematoma, penetration of atherosclerotic ulcers (PAU) and traumatic injury to the aorta; pseudoaneurysm; aortic rupture; Marfan syndrome; and congenital abnormalities such as coarctation of the aorta. One of the aortic diseases that cause the death rate to increase according to the 2010 Global Burden Disease is aortic aneurysm. Abdominal aortic aneurysm (AAA) is a focal dilatation of the aortic segment. The diagnosis of AAA is done by history taking, physical examination and supporting examination. Management at AAA aims to prevent aortic wall rupture. An alternative procedure without open surgery is endovascular aortic repair (EVAR) using prostheses. It is expected that through the EVAR method, mortality and morbidity due to AAA can be reduced. Keywords: abdominal aortic aneursym, EVAR, prostheses Â Â Penyakit aorta merupakan kumpulan penyakit pada aorta yang meliputi aneurisma aorta; sindrom aorta akut berupa diseksi aorta, hematoma intramular, penetrating atherosclerosis ulcer (PAU) dan cedera akibat trauma pada aorta; pseudoaneurysm; ruptur aorta; sindrom Marfan; serta penyakit kongenital seperti koarktasio aorta. Salah satu penyakit aorta yang menyebabkan angka kematian meningkat menurut Global Burden Disease 2010 adalah aneurisma aorta. Aneurisma aorta abdominalis (AAA) merupakan dilatasi fokal pada segmen aorta. Penegakan diagnosis AAA dilakukan dengan anamnesis, pemeriksaan fisik dan pemeriksaan penunjang. Penatalaksanaan pada AAA bertujuan untuk mencegah pecahnya dinding aorta. Prosedur alternatif tanpa pembedahan terbukaÂ yang dijadikan pilihan adalah endovascular aortic repair (EVAR) menggunakan protesa. Diharapkan melalui metode EVAR angka mortalitas dan morbiditas akibat AAA dapat diturunkan. Kata kunci: aneurisma aorta abdominalis, EVAR, protesa